Penanganan Sign On dan Sign Off Crew pada Kantor Syahbandar oleh PT. Seroja Jaya Agensi Cabang Kuala Tanjung - Benri Hamonangan Sitanggang; Nurmaliana Sari Siregar (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
Handling crew sign on and sign off starts from the moment the crew arrives at the PT office. Seroja Jaya Agensi Kuala Tanjung branch to sign Maritime Work Agreement (PKL) for seafarers who will join Indonesian flag ships and agreements for seafarers who will join foreign flag ships.This paper aims to determine the handling of crew sign on and sign off at the Harbor Master's office by PT. Seroja Jaya Agensi Kuala Tanjung branch which was started after a direction from the owner that there would be a crew change activity, after that the crew sign on and sign off process was carried out at the Harbor Master's office.This research was carried out at PT. Seroja Jaya Agensi Kuala Tanjung branch while carrying out Land Practice (PRADA) from January 2024 to July 2024. The problems faced in handling crew sign on and sign off at the Harbormaster's office were late notification given by the ship owner to the agent and intentional communication between the agent and the ship's crew who will sign on the seafarer's book.